2020
DOI: 10.21470/1678-9741-2019-0121
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vaccinium Myrtillus in the Prevention of Renal Injury in an Experimental Model of Ruptured Abdominal Aortic Aneurysm

Abstract: Objective: To examine the biochemical and histopathological renal effects of ischemia/reperfusion (I/R) injury using a ruptured abdominal aortic aneurysm (RAAA) model in rats and to investigate the potential protective effects of whortleberry (Vaccinium myrtillus). Methods: Thirty-two male Sprague-Dawley rats were randomly assigned into four groups-control, sham (I/R+glycerol), I/R, and I/ R+whortleberry. Midline laparotomy alone was performed in the control group. Atraumatic abdominal clamps were attached und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…Bilberry has been reported to reduce oxidative stress developing in tissues such as the kidney, ovary, and retina in various experimental models (17,26,27). In addition, Jakesevic et al reported that BB reduced oxidative stress-related intestinal inflammation and mucosal damage resulting from ischemia-reperfusion, and Widen reported that it ameliorated gingival inflammation (28,29).…”
Section: Histopathological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilberry has been reported to reduce oxidative stress developing in tissues such as the kidney, ovary, and retina in various experimental models (17,26,27). In addition, Jakesevic et al reported that BB reduced oxidative stress-related intestinal inflammation and mucosal damage resulting from ischemia-reperfusion, and Widen reported that it ameliorated gingival inflammation (28,29).…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…It contains numerous antioxidant compounds, including quercetin, resveratrol, catechins, vitamin C, phenolic acid, and anthocyanins (13,15). Due to these compounds, and particularly anthocyanins, BB exhibits antioxidant and anti-inflammatory effects (13,16,17).…”
Section: Introductionmentioning
confidence: 99%